2019
DOI: 10.1159/000501028
|View full text |Cite
|
Sign up to set email alerts
|

Management of Patients with Patent Foramen Ovale and Cryptogenic Stroke: An Update

Abstract: Patent foramen ovale (PFO) is a common benign finding in healthy subjects, but its prevalence is higher in patients with stroke of unclear cause (cryptogenic stroke). PFO is believed to be associated with stroke through paradoxical embolism, and certain clinical and anatomical criteria seem to increase the likelihood of a PFO to be pathological. Recent trials have shown that closure of PFO, especially if associated with an atrial septal aneurysm and/or a large interatrial shunt, may reduce the risk of recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 68 publications
0
48
0
2
Order By: Relevance
“…Until recently, PFO closure was not considered a risk reducing procedure for recurrent stroke [29,[38][39][40]. New trials in 2017-2018 questioned this policy and suggested considering PFO closure in addition to lifelong antiplatelet treatment in selected patients [41,42]. These results may again raise the yield of TEE in upcoming years.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, PFO closure was not considered a risk reducing procedure for recurrent stroke [29,[38][39][40]. New trials in 2017-2018 questioned this policy and suggested considering PFO closure in addition to lifelong antiplatelet treatment in selected patients [41,42]. These results may again raise the yield of TEE in upcoming years.…”
Section: Discussionmentioning
confidence: 99%
“…One feared outcome of venous thromboembolism in the setting of patent foramen ovale (PFO) is paradoxical stroke (4). The present report describes a novel case of concomitant aspiration thrombectomy and PFO closure in a patient with a right atrial thrombus and paradoxical embolic stroke.…”
mentioning
confidence: 87%
“…Since the development of percutaneous device closure of PFO as a potential therapeutic option in this group of patients, PFO closure is known to be beneficial as compared to medical therapy in the preventions of recurrent neurological events [ 3 ]. The role of echocardiography is very important both in the diagnosis of PFO and in the evaluation of PFO for transcatheter closure [ 4 , 5 ]. Transesophageal echocardiography (TEE) is considered the gold standard for the diagnosis of PFO because it provides anatomical details [ 6 ].…”
Section: Introductionmentioning
confidence: 99%